-4 + 10 + 6a - 2a + 3 9 + 4a
5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9
The value of a in the equation 5a plus 2a = 6-6a is a=6/11.
6a to the second power minus 8ab + 2a
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1
2a*3 = 8+4a 6a = 8+4a 6a-4a = 8 2a = 8 a = 4
6a squared-8ab+2a factor completely and check mentally
2a² + 6a
6a-3=8a+11 -3-11=8a-6a -14=2a a=-7
Since the question is 3(2a), then just write it out. 3(2a) is 2a+2a+2a or 6a.
= 2a - 10
With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)
If you mean -2a+6a then it simplifies to 4a
if f(x) = 3x - 10, then whatever is put (substituted) for x in the "f(x)" bit is substituted for x in the "3x - 10" bit. Thus f(2a) = 3(2a) - 10 = 6a - 10.
6a+1=2a+25 Subtract 2a from both sides 4a+1=25 Subtract 1 from both sides 4a=24 Divide both sides by 4 a=6 That is your final answer.
(2a - 3)(3a - 4)
6a - 8 - 4a - 2 → 6a - 4a - 8 - 2 → 2a - 10